Evaluation of stress and strain on mandible caused by changing the bar material in hybrid prosthesis utilizing “All-on-Four” technique - Yomna H. Shash; Mohamed T. Elwakad; Mohamed A. A. Eldosoky; Mohamed M. Dohiem (Alexandria Engineering Journal, 2023)
Full edentulism is the complete loss of teeth which affects mastication. The treatment is performed by using the hybrid prostheses to restore the mastication mechanism. The materials of choice for the bar in the hybrid prostheses are titanium and gold. The limitations of metals encourage the researchers to find alternatives materials. This research investigated the possibility of using ceramics, polymers and composites as a bar material instead of titanium. 3D model of mandible with hybrid prosthesis was stimulated with different bar materials. The von Mises stress of each part was extracted, besides the max& min principal stresses /strains were computed for the bone parts. By using PEEK bar, the von Mises stresses on cortical and cancellous bones reduced by (3.4&3.02 %) and (10.4 &3.36 %) under unilateral and bilateral forces, besides the mucosa stress increased to 0.121 and 0.135 MPa respectively. For all used materials, the stresses and strains of bone parts did not exceed the critical limits, besides the mucosa stress was lower than the pain threshold value. As a consequence, it was concluded that all materials included in this study could be used as an alternative to titanium as a bar material.